The Difference Between Narration and Citing as Evidence According to Hadith Scholars (Comprehensive Journal of Science, 2026)
This research aims to clarify the concepts of narration and citation, tracing the usage of these two terms by the imams and highlighting their practical applications. It also explores the extent of the difference between them and clarifies the point of contention among scholars regarding this subtle issue. Neglecting this distinction leads to a misunderstanding of the imams' work and their hadith methodologies as presented in their writings. Furthermore, it examines the impact of this distinction on deriving legal rulings, how the imams differentiated between primary and secondary hadiths, and the implications of this distinction for the validity of a hadith as evidence. Finally, it explores the influence of critical methodologies in terminology and linguistic expression on the establishment of the validity of a hadith as evidence and the concept of hadith narration. The research is significant in clarifying the terminology that influences hadith and critical studies.
Keywords: Differences – Narrations – Arguments – Hadith – Principles – Follow-ups – Evidence.